ANKK1 and TH gene variants in combination with paternal maltreatment increase susceptibility to both cognitive and attentive impulsivity - Palumbo, Sara; Mariotti, Veronica; Vellucci, Stefano; Antonelli, Klizia; Anderson, Nathaniel; Harenski, Carla; Pietrini, Pietro; Kiehl, Kent A.; Pellegrini, Silvia (Frontiers in Psychiatry, 2022)
Recent scientific findings suggest that dopamine exerts a central role on impulsivity, as well as that aversive life experiences may promote the high levels of impulsivity that often underlie violent behavior. To deepen our understanding of the complex gene by environment interplay on impulsive behavior, we genotyped six dopaminergic allelic variants (ANKK1-rs1800497, TH-rs6356, DRD4-rs1800955, DRD4-exonIII-VNTR, SLC6A3-VNTR and COMT-rs4680) in 655 US White male inmates convicted for violent crimes, whose impulsivity was assessed by BIS-11 (Barratt Impulsiveness Scale). Furthermore, in a subsample of 216 inmates from the whole group, we also explored the potential interplay between the genotyped dopaminergic variants and parental maltreatment measured by MOPS (Measure of Parental Style) in promoting impulsivity. While we did not find any direct association between any of the studied genetic variants and impulsivity, we did observe a significant interaction among paternal MOPS scores, ANKK1-rs1800497-T allele and TH-rs6356-A allele, which increased the variance of BIS-11 cognitive/attentive scores explained by paternal maltreatment from 1.8% up to 20.5%. Our data suggest that paternal maltreatment increases the risk of attentive/cognitive impulsivity and that this risk is higher in carriers of specific dopaminergic alleles that potentiate the dopaminergic neurotransmission. These findings add further evidence to the mutual role that genetics and early environmental factors exert in modulating human behavior and highlight the importance of childhood care interventions.